Heart Size Evaluation of Indonesian Domestic House Cat by Motion Mode Echocardiography Imaging - DENI NOVIANA; LYNN KAAT LAURA KURNIAWAN (Bogor Agricultural University, Indonesia, 2013)
Indonesian Domestic House Cats (DHC) are prone to various diseases, especially cardiovascular diseases. Physical examination alone is not enough to differenciate cardiac diseases, which is why further screening tests such as heart ultrasonography-echocardiography are needed. Since there has been no information regarding the heart size of Indonesian DHC, the purpose of this study was to determine the heart size of an anesthetized Indonesian DHC through Motion mode echocardiography imaging. Nine male cats weighing between 3.3-3.4 kg were anesthetized using zolazepam-tiletamine. Echocardiographic examinations were taken on the right parasternal short axis view at the papillary muscle and aorta level using a 7.5 MHz transducer. Result showed that the wall thickness, left ventricular internal diameter and fractional shortening of the Indonesian DHC were similar compared with those in other cat breeds with the same average weight. The left atrium internal diameter and the aorta diameter of the Indonesian DHC were relatively smaller. However, the left atrium and aorta diameter ratio were similar to the result in other cat breeds with the same average weight. Through this study, we also could specify the left ventricular volume, stroke volume, cardiac output and ejection fraction that not yet reported before.